2018
DOI: 10.1038/s41419-017-0012-9
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress preconditioning of mouse perivascular myogenic progenitors selects a subpopulation of cells with a distinct survival advantage in vitro and in vivo

Abstract: Cell engraftment, survival and integration during transplantation procedures represent the crux of cell-based therapies. Thus, there have been many studies focused on improving cell viability upon implantation. We used severe oxidative stress to select for a mouse mesoangioblast subpopulation in vitro and found that this subpopulation retained self-renewal and myogenic differentiation capacities while notably enhancing cell survival, proliferation and migration relative to unselected cells. Additionally, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
582
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 679 publications
(601 citation statements)
references
References 41 publications
15
582
4
Order By: Relevance
“…In summary, we revealed an overexpression of ECM components, which are associated with enhanced migratory capacities of tumour cells ( TNC [ 76 , 77 ], FN1 [ 78 ]), resistance to chemotherapy ( COL11A1 [ 43 , 75 ], SPP1 [ 79 ]) and adverse outcome ( COL11A1 [ 42 ], TNC [ 80 ], FN1 [ 78 ]) in other primaries. The functional role of these molecules and their potential as therapeutic targets are currently under intense investigation [ 65 , 66 , 75 , 79 , 81 , 82 ]. Hence, as new therapeutic approaches for SGC are needed, our findings are of high translational relevance.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, we revealed an overexpression of ECM components, which are associated with enhanced migratory capacities of tumour cells ( TNC [ 76 , 77 ], FN1 [ 78 ]), resistance to chemotherapy ( COL11A1 [ 43 , 75 ], SPP1 [ 79 ]) and adverse outcome ( COL11A1 [ 42 ], TNC [ 80 ], FN1 [ 78 ]) in other primaries. The functional role of these molecules and their potential as therapeutic targets are currently under intense investigation [ 65 , 66 , 75 , 79 , 81 , 82 ]. Hence, as new therapeutic approaches for SGC are needed, our findings are of high translational relevance.…”
Section: Discussionmentioning
confidence: 99%
“…Herein, we revealed that hsa_circ_0039053 could serve as the ceRNA of miR-637 to increase USP21 expression in HCC. Previous studies demonstrated that miR-637 exerted the tumor-inhibitory roles in diverse human tumors, such as cervical cancer, colorectal cancer, and gastric cancer 23 - 25 . In consistence of previous studies, we also observed that miR-637 was reduced in HCC and the elevation of miR-637 was linked to poor disease outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Lipopolysaccharide (LPS) is widely localized in the outer cell wall of Gram-negative bacteria. Thus, LPS elicits a host inflammatory response that results in increased production of chemokines, cytokines, and pro-inflammatory mediators by the immune system [ 10 ]. Macrophages exposed to LPS during microorganism infections stimulate the immune system to produce cytokines and chemokines, followed by inflammatory events.…”
Section: Introductionmentioning
confidence: 99%